2016
DOI: 10.1530/edm-15-0114
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone replacement in 49,XXXXY syndrome: andrological, metabolic and neurological aspects

Abstract: SummaryWe report the case of a 19-year-old boy, presenting several congenital malformations (facial dysmorphisms, cardiac and musculoskeletal abnormalities), mental retardation, recurrent respiratory infections during growth and delayed puberty. Although previously hospitalised in other medical centres, only psychological support had been recommended for this patient. In our department, genetic, biochemical/hormonal and ultrasound examinations were undertaken. The karyotype was 49,XXXXY, a rare aneuploidy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…(Gropman et al., 2010; Sumathipala, Gamage, Wijesiriwardena, Jayasekara, & Dissanayake, 2012). Ultrasound findings including cystic hygroma, polyhydramnios, small penis and abnormal posturing might be suggestive of this condition (Mazzilli et al., 2016; Schluth et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Gropman et al., 2010; Sumathipala, Gamage, Wijesiriwardena, Jayasekara, & Dissanayake, 2012). Ultrasound findings including cystic hygroma, polyhydramnios, small penis and abnormal posturing might be suggestive of this condition (Mazzilli et al., 2016; Schluth et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Mazzilli et al. (2016) reported androgen treatment on a 19‐year‐old boy with a 49, XXXXY syndrome. The study reported normalisation of testosterone levels, an increase in testicular volume, an increase in penile size and an increase in pubic hair growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Males with 49,XXXXY typically undergo testosterone treatment ( T ) to promote optimal sexual and neurocognitive development [ 37 ]. First, scores on the CBCL and BRIEF were compared between the 49,XXXXY no- T and 49,XXXXY T groups.…”
Section: Resultsmentioning
confidence: 99%
“…There was also an increase in pubic hair growth, testicular volume and penis size, weight loss, homeostatic model assessment index reduction, and the normalization of vitamin D values. Moreover, the patient showed greater interaction with the social environment and context (Mazzilli et al 2016).…”
Section: Genetic Counselingmentioning
confidence: 96%